SKRINING FITOKIMIA DARI SENYAWA METABOLIT SEKUNDER BUAH JAMBU BIJI MERAH (Psidium guajava L.) - Siti Nurlani Harahap; Nurbaity Situmorang (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
Guava (Psidium guajava L.) is a tropical plant come from southern Mexico and Central America. Red guava fruit has many benefits, one of them is to control fruit fly pests on plants. In red guava fruit is presumed to contain secondary metabolite compounds can be used as natural attractants for fruit fly pests. This study aims to determine the content of secondary metabolite compounds found in red guava (Psidium guajava L.). This research used the qualitative experimental methods. The research started with processing red guava fruit samples into the powder of simpilisa. The powder of simplicia was then macerated with methanol as a solvent at a ratio of 1: 3 for + 5 days. The maceration result was extracted again by rotary evaporator to obtain the concentrated extract. The concentrated extract was screened for phytochemicals to determine the metabolite compounds contained in the sample. The results showed that the secondary metabolites in red guava fruit (Psidium guajava L.) were positive for flavonoids, alkaloids, tannins / phenolics, terpenoids / steroids. whereas the saponin test showed negative results. We can concluded that guava fruit extract (Psidium guajava L.) contains flavanoids, alkaloids, terpenoids / steroids and tannins / phenolic.